Characterizing Treatment-Resistant Anorexia Nervosa - Smith, Sarah; Woodside, D. Blake (Frontiers in Psychiatry, 2021)
Background: The issue of treatment resistance in eating disorder care is controversial. Prior research has identified multiple failed treatment attempts as a common criterion for severe and enduring anorexia nervosa, but little is known about patients who have multiple failed treatment attempts. This study was designed to compare the clinical and demographic characteristics of eating disorder patients with multiple, incomplete inpatient admissions to those with good outcomes. Understanding if these patient populations differ at initial admissions has implications for the prediction, and characterization of, inpatient eating disorder treatment resistance. Methods: This study analyzed existing data from a specialist inpatient eating disorder program at a large Canadian teaching hospital collected between 2000 and 2016. Treatment resistance was defined as two or more incomplete admissions and no complete admissions in the study period. Data was available on 37 patients who met this criteria, and 38 patients who had completed their first admission and remained well (defined as a BMI >18.5 with no binging or purging behavior) for one year after discharge. Variables of interest included age, weight, diagnoses, duration of illness, eating disorder psychopathology, eating disorder behavioral frequencies and depressive symptoms at the time of index inpatient admissions. Statistical analyses consisted of Mann-Whitney U tests, Chi-square tests and a logistic regression. Results: In our main bivariate analyses, patients with multiple incomplete admissions were characterized by more severe eating disorder psychopathology and depressive symptoms at admission as well as an increased prevalence of the binge purge subtype of anorexia nervosa. In our exploratory multivariate analyses controlling for diagnostic subtype and depressive symptoms, severity of eating disorder psychopathology did not remain significant. No statistically significant difference in body mass index (BMI) or frequencies of eating disorder behaviors were found. A trend towards a longer duration of illness did not meet statistical significance. Conclusions: This study found that patients considered resistant to inpatient eating disorder treatment differ from those with good outcomes at initial admission. These results suggest that while treatment resistant anorexia nervosa may be related to severe and enduring anorexia nervosa, it may also be a different concept that warrants additional research.